Evaluation of cholinesterase from the muscle and blood of anabas testudineus as detection of metal ions - Ahmad S.A.; Sabullah M.K.; Basirun A.A.; Khalid A.; Yasid N.A.; Iqbal I.M.; Shamaan N.A.; Syed M.A.; Shukor M.Y. (Parlar Scientific Publications, 2024)
Indexed by Scopus/WOS